Consulta de enfermagem baseada no autocuidado apoiado : benefícios no manejo e controle do Diabetes mellitus - Teston, Elen Ferraz (2015)
Type 2 Diabetes mellitus (T2DM) is a sensitive condition for primary care, which presupposes the organization and planning of actions by the health team. The nursing professional may foster the empowerment of the individual for self-care and disease management. The objective of this study was to assess the effect of nursing consultation underpinned by the self-care supported in disease management and control by people with T2DM. The study, held in a small town, located in the north side of the Paraná state, has involved two methodological strands and was developed in three steps: cross-sectional study, with a quantitative approach, qualitative study and randomized clinical trial. The data collection of the cross-sectional study was conducted from March to September 2014, which included 288 individuals with T2DM among those enrolled in the six Basic Units of the town, randomly selected and in a stratified way, with the purpose of identifying the knowledge and the attitude towards the disease and associated factors.It was observed that being a man, having low schooling level, lack of complications derived from T2DM, not having undergone consultation with an endocrinologist in the last 12 months and having good adherence to drug treatment have been configured in factors associated with inadequate knowledge about the disease. In turn, the items ?income greater than two minimum wages?, ?increased waist circumference? and ?fail to undergo blood exams in the last six months? were associated with a negative attitude towards the disease. The qualitative data were collected with 18 individuals among those who attended the crosssectional study, through semi-structured interview, after being submitted to content analysis in its thematic modality. The results have shown that individuals recognize their responsibility for developing self-care actions: performing food control, practicing physical exercises, reducing stress and adhering to drug treatment. Nevertheless, some of them justify the fail to conduct these actions because of external factors related to health service organization, family and work environment.Lastly, the nursing intervention (which includes three nursing consultations and two monitoring phone calls, with basis on the supported self-care), lasted for five months (June-October 2014) and was held in the BHU of the town with the largest number of individuals with T2DM who were enrolled. The number of individuals to be included in the study was defined from sample calculation, taking into account the standard deviation for glycated hemoglobin. The 134 individuals were randomly divided into two groups: intervention - IG (67) and control group - CG (67). Data analysis has shown that the intervention provoked significant increase of knowledge, positive attitude towards the disease, impact on quality of life and adherence to self-care activities. Moreover, with regard to laboratory parameters and anthropometric data, the intervention group has shown a significant decrease of blood glucose values, glycated hemoglobin levels, weight, waist circumference and blood pressure levels. Lastly, it was observed a positive effect on health behaviors because individuals of the intervention group were more prone to conduct glucose monitoring (OR: 3,5), food control (OR: 2,7) and regular physical activity (OR: 3 9). Accordingly, it is concluded that the intervention based on the supported self-care was effective to improve the management and control of T2DM.